Pola Peresepan Obat Antihipertensi pada Pasien BPJS Kesehatan dibeberapa Apotek Daerah Bandung Periode November 2023 - Dinda Juliana; Dika Pramita Destiani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension is a non-communicable disease that always increases every year. Hypertension is known as a silent killer because patients who suffer from hypertension rarely feel the symptoms. Common symptoms of hypertension can be headaches in the back of the neck, blurred vision, and others. The blood pressure of hypertension sufferers is above 140/90 mmHg. This study aims to see the pattern of prescribing antihypertensive drugs in BPJS Kesehatan patients including gender, age, patient diagnosis, and combination of antihypertensive drug classes. The method used is descriptive observational research. This study was conducted using 195 prescriptions in the period November 2023. The results obtained were that hypertension sufferers were more dominated by women with a total of 131 sufferers with a percentage of 67% compared to men with a total of 64 sufferers with a percentage of 33%. The age most affected by hypertension is people aged 51 years - 75 years with a total of 143 people and a percentage of 73.33%. 92 of 195 (47.18%) patients did not have other diseases such as diabetes mellitus, hyperlipidemia, heart, GI, and asthma. Single therapy of antihypertensive drugs was most commonly prescribed by doctors with a total of 127 patients with a presentation of 65.13% compared to patients who used combination therapy of two or more antihypertensive drugs. Calcium antagonist or CCB drugs were most commonly used by BPJS patients at several pharmacies in the Bandung area used in the prescription analysis with a total of 107 patients with a percentage of 54.87%.